Reactive improvement of environmental policies: lessons from the Mariana and Brumadinho disasters - Braga, Michelle Cristina dos Reis; Fonseca, Alberto de Freitas Castro (Sustainability in Debate, 2022)
The State is not always able to proactively improve environmental policies. Eventually, policy improvements are a result of disasters that expose pre-existing problems. This situation is reflected in the state of Minas Gerais (Brazil), where, after the failures of the Fundão and B1 tailings dam, in Mariana and Brumadinho, several problems in dam safety and emergency policies were exposed. This study had a twofold objective: 1) to identify the mechanisms used by the government of Minas Gerais to improve environmental policies, and 2) to understand how the Mariana and Brumadinho’s disasters affected dam safety and emergency policies. Based on semi-structured interviews and regulatory analysis, the study revealed that the state government of Minas Gerais has been predominantly reactive in controlling environmental policies. Additionally, it was observed that the disasters catalysed a learning process that culminated in potentially better dam safety policies.